1988
DOI: 10.3177/jnsv.34.55
|View full text |Cite
|
Sign up to set email alerts
|

Mineral contents in model diet samples for different age groups.

Abstract: SummaryModel diet samples of eight groups (3,16, 40, and 70 years old for both sexes), were analyzed for sodium, potassium, phosphorus, calcium, magnesium, iron, zinc, manganese, aluminum, copper, barium, nickel and molybdenum by using inductively-coupled plasma atomic emission spectrometry (ICP-AES). Mineral intakes for 3 year olds were lower than those of other age groups because total food consumption was less. The intake of major elements, Na, K, P, Ca, and Mg, varied within about 20% of each other. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…In 1986. Shiraishi et d. 15 reported that the Mg intake in Japanese adults is 270 mg/day, and this is adequate as it is almost the recommended intake level. But recently in Japan, the dietary Mg level has decreased especially in young people because of Americanized eating habits: excess intake of meats and snacks, and less intake of vegetables.…”
Section: Correlation Between Growth and Magnesiummentioning
confidence: 97%
“…In 1986. Shiraishi et d. 15 reported that the Mg intake in Japanese adults is 270 mg/day, and this is adequate as it is almost the recommended intake level. But recently in Japan, the dietary Mg level has decreased especially in young people because of Americanized eating habits: excess intake of meats and snacks, and less intake of vegetables.…”
Section: Correlation Between Growth and Magnesiummentioning
confidence: 97%
“…We have been studying the dietary intake for a Reference Japanese Man against the Reference Man, which were reported by the International Commission on Radiological Protection (ICRP) as the selected values for Western Europeans and North Americans (1). Most of our previous data were obtained by inductively coupled plasma atomic emission spectrometry (ICP-AES) (2)(3)(4)(5). Now, a newer, more powerful technique for trace elements, inductively coupled plasma mass spectrom etry (ICP-MS), is available (6).…”
mentioning
confidence: 99%
“…Uma breve discussão foi realizada sobre a estimativa da ingestão diária de MPs através da taxa de consumo dos alimentos. (SHIRAISHI et al, 1988;TSOUMBARIS;TSOUKALI-PAPADOPOULOU, 1994;BRÄTTER et al, 1995;BIEGO et al, 1998;DANG, 1998;LAURIA;PORTO DA SILVEIRA, 2004).…”
Section: Ingestão Diária De Metais Pesados Essenciaisunclassified